Faktor-Faktor Yang Mempengaruhi Produksi Industri Mikro Dan Kecil (IMK) Di Kota Denpasar - Kardha, Putu Jata Tresna Yoga; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
Denpasar city is the capital city of Bali regency and one of the economycentral in Bali. One of the economic supporting sector in Denpasar city is industries sector, where many society runs their business in small-micro entrepeneurship (SME). This research’s aim to determine the influence of type of electricity, amount of electricity, amount of labours, amount of  machines, operational hours, capital, the education of SME’s owner, and business duration variables towards the productions of SME’s. This research took place in Denpasar city, that Denpasar as municipality there is many SME’s growing there. The sample of this research is about 50 SME using the proportionate random samplingmethod. The analytical technique used in this research is multiple linear analysis technique. Base from the results of the analysis showed that type of electricity, amount of electricity, amount of labours, amount of machines, operational hours, capital, the education of SME’s owner, and business duration variables are positively and significantly influenced simultaneously towards theproduction of SME’s. As partially the amount of labours, and operational hours variables are positively and significantly influenced the productions of SME’s, while type of electricity, amount of electricity, amount of machines, capital, the education of SME’s owner, and business duration variables are not influenced the productions of SME.   Keywords : production, SME’s characteristics, capital